PENGARUH PENGALAMAN, INDEPENDENSI , DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT DENGAN ETIKA SEBAGAI VARIABEL PEMODERASI (Studi Empiris pada Auditor di KAP Bandung) - Nurhayati, Enung (Jurnal Riset Keuangan dan Akuntansi, 2015)
This researchexamine how ethics has an effect in moderating the Experience, Independence and Time Budget Pressure on Audit Quality. Descriptive and verificative method is used in this research. The population in this study is the auditor who works at KAP Bandung, whileÃ‚Â  the technique to determine the number of samples using the formula Yamane obtained 142 respondents . Questionnaires distributed for 142 respondents were returned by them are 74, while the questionnaire which can be further processed as many as 69. MRA( Moderated Regression Analysis) is used to analyze the data.The result of this research show that experience, independence and time budget pressure simultaneously have an effect on audit quality. While, partially the experience and independence have a positive effect on audit quality, and time budget pressure has a negativeeffect on audit quality. Then,ethicshas a significant effect in moderating the experience, independence, and time budget pressure on audit quality.